Evaluasi Program PAUD Holistik Integratif Dengan Model CIPP DI TK Satu Atap Sejiram Sambas - Saripah Saripah; Siti Mania; Muhammad Nur Akbar Rasyid (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study aims to evaluate the implementation of the Holistic Integrative Early Childhood Education (PAUD HI) Program at TK Satu Atap Sejiram, Sambas Regency. The research method used is an evaluation study employing the CIPP model (Context, Input, Process, and Product). Data collection instruments include interview guidelines, observation, and documentation. The study involved five individuals namely the principal, a teacher, a parent, a healthcare worker, and the head of the Education Office as well as 20 students. The evaluation results show that in the context component, the program aligns with the community’s understanding of government policy and the need for the implementation of the Holistic Integrative PAUD program. In the input component, it was found that human resources still need improvement, particularly in terms of teacher training and cross-sector involvement. The process evaluation shows integration of services in education, health, and nutrition, although parental involvement has not yet been optimal. In the product evaluation, the program demonstrates positive development in children across various developmental domains, including religious and moral values, cognitive, physical-motor, language, arts, and socio-emotional aspects. Overall, the evaluation of the Holistic Integrative PAUD program at TK Satu Atap Sejiram in Sambas highlights the need for stronger local policy support, particularly regarding the integration of education, health, nutrition, and child protection services. Practically, this program evaluation is useful for reinforcing more specific regional policies to support the implementation of Holistic Integrative PAUD in border areas, including adequate budget allocation and technical regulations that promote cross-sector collaboration